PENGEMBANGAN POTENSI WISATA BAHARI BERBASIS MASYARAKAT DI PULAU PASARAN, BANDAR LAMPUNG - Nuning Mahmudah Noor (Inovasi Pembangunan : Jurnal Kelitbangan, 2021)
Pasaran Island is not only well-known as a major producer of anchovies in Lampung province, but also as a mariculture location of some fish and green mussel. The island which only covers ​​12.5 hectares is located in urban areas, in Bandar Lampung City, the capital of Lampung province. Pasaran Island has the potential as a fishery production center and marine tourism (minawisata). The minawisata concept emphasizing the active role and rights of the local communities in the management of tourism in their area (community-based marine tourism). Several programs for the development of minawisata on Pasaran island have been successfully implemented, including: designing minawisata, enhancing sanitation, strengthening institutions, building facilities and infrastructure, developing fishery products, and strengthening promotions. Pasaran Island would therefore be a new marine-tourism icon that beneficial to Bandar Lampung City and directly boost the local community's welfare.